Wonder Woman [videorecording (Blu-Ray)] - Snyder, Zack, 1966-; Heinberg, Allan; Fuchs, Jason, 1986-; Gadot, Gal, 1985-; Pine, Chris, 1980-; Wright, Robin, 1966-; Nielsen, Connie, 1965-; Huston, Danny, 1962-; Thewlis, David, 1963-; Anaya, Elena; Bremner, Ewen; Davis, Lucy, 1973-; et al. (Warner Brothers Entertainment Incorporated, 2017)
Before she was Wonder Woman she was Diana, princess of the Amazons, trained warrior. When a pilot crashes and tells of conflict in the outside world, she leaves home to fight a war to end all wars, discovering her full powers and true destiny.